Faraway blue - Evans, Max (Albuquerque University of New Mexico Press, 2005)
A fictionalized account of a real-life, 19th century black soldier who fought against the Indians in New Mexico. He is Moses Williams, an ex-slave serving as sergeant in the Ninth Cavalry, and facing him is the great Apache warrior, Nana
87316
Keywords: Williams, Moses -- d. 1899 -- Fiction; Nana -- Apache chief -- ca. 1806-1896 -- Fiction; United States. -- Army -- African American troops -- Fiction; United States. -- Army. -- Cavalry, 9th -- Fiction; Indians of North America -- Wars -- 1866-1895 -- Fiction; Warm Spring Apache Indians -- Wars -- Fiction; African American soldiers -- Fiction; New Mexico -- Fiction; Historical fiction; War stories